2021
DOI: 10.1371/journal.pcbi.1008414
|View full text |Cite
|
Sign up to set email alerts
|

Modelling thalamocortical circuitry shows that visually induced LTP changes laminar connectivity in human visual cortex

Abstract: Neuroplasticity is essential to learning and memory in the brain; it has therefore also been implicated in numerous neurological and psychiatric disorders, making measuring the state of neuroplasticity of foremost importance to clinical neuroscience. Long-term potentiation (LTP) is a key mechanism of neuroplasticity and has been studied extensively, and invasively in non-human animals. Translation to human application largely relies on the validation of non-invasive measures of LTP. The current study presents … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Drugs hypothesised to increase cortical excitability, such as 3-h post ketamine infusion and acutely following a dose of d-cycloserine, have a facilitatory effect on visual LTP 36 , 37 . However, there is evidence that increases in inhibitory activity occur in tandem with excitatory changes at different cellular layers of the visual cortex following LTP induction with a visual tetanus 38 . It is possible that previous contrasting findings are a result of different mechanisms being captured by different methods of understanding excitatory and inhibitory activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs hypothesised to increase cortical excitability, such as 3-h post ketamine infusion and acutely following a dose of d-cycloserine, have a facilitatory effect on visual LTP 36 , 37 . However, there is evidence that increases in inhibitory activity occur in tandem with excitatory changes at different cellular layers of the visual cortex following LTP induction with a visual tetanus 38 . It is possible that previous contrasting findings are a result of different mechanisms being captured by different methods of understanding excitatory and inhibitory activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A biologically grounded model of thalamo-cortical circuitry [ 34 ] has previously been used to build a neural mass model of human brain networks related to visual processing, such that the production of signal at the scalp is plausibly explained by alterations to the connectivity between and within cell populations in the thalamus and layers 2–6 of the visual cortex, as well as receptor time constants (open time and decay rate) of neurotransmitters [ 35 ]. Application of this thalamo-cortical model (TCM) to EEG LTP data without a drug condition has previously demonstrated modulation of connections consistent with in vivo LTP research, including increased excitatory connectivity between the thalamus and layer 4 neurons in the visual cortex, as well as from layer 4 to layers 2/3 [ 36 ], but has not yet been applied to microdoses of LSD.…”
Section: Introductionmentioning
confidence: 94%
“…In the current study, the finding of enhanced P2 potentiation on day 21 may plausibly represent a mechanism of greater excitation or reduced inhibition underlying preserved cyclicity of LTP increases in the perimenstrual-like phase. Previous studies have shown that generative, neurobiologically informed models of cortical activation during EEG can be used to disentangle these possibilities after administration of drugs [57][58][59][60] and in disorder [61,62], as they have demonstrated sensitivity to the change in visual cortex microcircuitry that underlie LTP [35] and change over the menstrual cycle [63].…”
Section: The Effect Of Preserved Cyclicitymentioning
confidence: 99%
“…AMPA, NMDA, GABA-A, GABA-B, M and H channels are also parameterised. This model has previously demonstrated sensitivity to (invasively demonstrated [37, 38]) changes to the visual cortex evoked by LTP [35].…”
Section: Introductionmentioning
confidence: 99%